FAKTOR YANG BERKONTRIBUSI PADA KEIKUSERTAAN SEKTOR FORMAL DALAM SKEMA ASURANSI KESEHATAN SOSIAL: NARRATIVE REVIEW - Idris, Haerawati (UI Scholars Hub, 2023)
Countries worldwide have been working towards achieving universal health coverage target, including countries with low and middle incomes. Even though it is mandatory, the formal sector does not automatically become a participant in social health insurance. This study describes the factors contributing to formal sector participation in social health insurance. This study uses a narrative review approach. This study focuses on the factors that contribute to the participation of the formal sector in social health insurance schemes. We identified articles selected according to the inclusion criteria covering the formal sector, English and Indonesian, adopting social insurance, and open access articles. We then collect selected articles and synthesize the factors that contribute to formal sector participation in social health insurance schemes. We found that the formal sector's participation in social health insurance is related to the following factors: the mandatory scheme, knowledge of the business sector/company, company finances, type of company, risks that the company may experience, and perceptions of the quality of health services provided. This study found several factors that contribute to the participation of the business sector in social health insurance. Factors that are structural/policy in nature, knowledge of social insurance policies, and service quality from the supply side need to be of concern to the government in efforts to expand to this group